Tafseer Al-Maidah verse 6: Purification (Ablution) in Islam is a Simple Cleansing Procedure that uses Water or Dust as Hygiene Agents to combat COVID-19 - Abdullah A Afifi (IDRIS Darulfunun Institute, 2022)
COVID-19 as a pandemic was both disturbing and shocking. While people were so confused and lost direction on how to deal with it, they also panicked and tried every way to make themselves and their relatives safe. People develop procedures that require advanced equipment to support those high-cost and complex procedures. People prioritize cleanliness in order to maintain a safe environment. Elaborating tafseer Al-Maidah verse 6 can be a constructive alternative to maintaining cleanliness. The cleanliness standard procedure in Islam was simplified, but it maintained obedience's deep meaning. Ablution (wudu) is the main procedure with preconditions and also offers alternatives for specific conditions. Water and dry sand (clean earth) are hygiene agents for cleanliness procedures and purification.